Quantitative Identification of Pulse-Like Ground Motions Based on Hilbert–Huang Transform - Zhen Liu (Shock and Vibration)
Aiming to address the problem of pulse-like ground motions being difficult to identify, this paper refines the Baker’s wavelet-based pulse-like ground motions identification method, followed by a new pulse-like ground motion identification method based on Hilbert–Huang Transform (HHT) being proposed. In this method, HHT is used to decompose ground motions instead of wavelet. HHT can overcome the dependence of wavelet analysis on the selection of mother wave, and thus more complex velocity pulses can be identified. In order to compare the effects of two pulse-like ground motion identification methods, HHT-based method and wavelet-based method, respectively, are used to identify ground motions in Pacific Earthquake Engineering Research Center (PEER). After identifying the 3066 groups of ground motions selected from PEER, it is found that the HHT-based method can identify 229 pulse-like ground motions, and the wavelet-based method can identify 150 pulse-like ground motions. More complex shapes of near-fault velocity pulses can be extracted by the HHT-based method. By analyzing the seismic response, fault distance, and cumulative squared velocity (CSV) of these pulse-like ground motions, it is found that the pulse-like ground motions identified by the HHT-based method have strong near-fault characteristics. If a high recognition quality can be guaranteed, the proposed HHT-based method can identify many kinds of near-fault velocity pulses and thus provide more pulse-like ground motions for seismic researches.